Contextual violence, cyberbullying, and posttraumatic stress symptomatology in university students in Ciudad Juárez, Chihuahua - Nieves González Valles, María (Consorcio de Universidades Mexicanas A.C., 2019)
In recent years, Mexico’s northern border has seen unprecedented levels of social violence. With this as the backdrop of our research study, the objective was to analyze the relationship between the frequency of exposure to community or contextual violence and violence through electronic means, and some indicators of posttraumatic stress in young university students from Ciudad Juárez. Through a cross-sectional, quantitative, correlational study, three self-report instruments were applied to 300 university students. Significant relationships between experiences of exposure to community or contextual violence, cyberbullying, and post-traumatic stress symptomatology were identified. The scales were found to be reliable (with an alpha greater than a=.748). Twenty-two percent of students who reported at least one act of violence against themselves, against family members or close friends, and/or online, also reported experiencing two or more indicators of posttraumatic stress. Statistically significant positive correlations were found between exposure to contextual violence in schools, neighborhoods, and places of leisure, and cyberbullying. Similarly, there were significant correlations between direct and indirect violence and posttraumatic stress symptomatology, primarily in brick-and-mortar schools and entertainment centers.